Civil Society: Pembangun dan Sekaligus Perusak Demokrasi - Hadiwinata, Bob Sugeng (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2005)
Disillusions with the limits of parliamentary politics and the increasingly dilapidated processes of party politics have generated a renewed interest on civil society as a means of rejuvenating public life. In light of mounting animosity against the